Faktor-Faktor Yang Berhubungan Ankle Brachial Pressure Index Di Poli Penyakit Dalam RSUP. Dr. M Hoesin Palembang Tahun 2012 - Sukma Wicaturatmashudi (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2014)
DM disease have a very broad impact include disorders of the eyes (diabetic neuropathy), disorders of the kidneys (diabetic nephropathy) and foot (Susanto, 2010). The most dreaded complications and is a causa major disability, amputation and death is gangrene in the feet. Diabetic foot conditions can be observed by monitoring the Ankle Brachial Index (ABI) who see the difference of pressure on the arteries in the arms and legs.This research aims to know the factors that Relate Ankle Brachial Pressure Index At Polikliniik Penyakit Dalam M Hoesin Palembang in 2012. Research done by the method of cross sectional.Data analysis in this study uses the bivariat analysis and univariate test by using independent t test, pearson correlation and significance by degrees spearmann with a confident interval = 0.05. Although not found relationships between variables but given the substance of variables in this study is very important and it is recommended to patients with Diabetes Mellitus to do early detection of the risk of peripheral vascular disease by periodically checked the value of ankle brachial pressure index.